ANTIBACTERIAL ACTIVITY TESTING OF N-HEXANE FRACTION OF RED DRAGON (Hylocereus polyrhizus Britton & Rose) FRUIT PEEL ON Staphylococcus aureus ATCC 25923 - Sri Amalia; Sri Wahdaningsih; Eka Kartika Untari (Majalah Obat Tradisional, 2014)
Inappropiate antibiotic use was one of the main reason that caused pathogenic microorganism resistance, leads to ineffective treatment. One of those resistance bacteria is Staphylococcus aureus. The research for discovering new antibiotics can help with this issue. The peel of red dragon fruit (Hylocereus polyrhizus) is one of the plants that has antibacterial compounds. The aim of this research is to prove and determine the clear zone value of n-hexane fraction of red dragon fruit’s peel againts Staphylococcus aureus ATCC 2593. The peel was maserated with chloroform, then fractinated by n-hexane. Futhermore, the antibacterial properties of the fraction was tested using Disc Diffusion (Kirby-Bauer) methode with 20 and 40 mg/mL concentrations. Ampicillin used as control positive, and Dymetil sulfoxida (DMSO) used as control negative . Based on the phytochemical screening of the fraction, the n-hexane fraction of the dragon fruit’s peel contain terpenoid and alkaloid. Clear zones produced by 40 mg/mL is 12.80±1,69 mm and for 20 mg/mL is 11.17±1,11 mm.